Marketing Strategy to Increase Sales of Custom Built Furniture - Nugroho, Ardianto; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract - On the 2015 Asia Construction Outlook, 37 percent of the construction spending in Asia accomplished on infrastructure, 34 percent was spending on residential projects, and the rest is on non-residential projects. In 2013 Indonesia spending 27 billion dollars and became the fourth country with the largest spending on construction, below India, Japan and China. To accommodate the needs that are related to the construction sector, PAZEUL was established in 2013 with specialty on interior design and architecture. During the beginning the company faced issues such as a different level of quality amongst products, high production costs, no growth for a period of time and a delayed process of manufacturing furniture. On the external analysis, the consumer has a power of bargaining especially in price negotiation, mainly because of no appreciation from the public about the role of designer and architect, our problem as a design consultant where there are no standard in determining the appropriate design fee, and various substitute furniture products appear in the market. Based on the 7P marketing mix, PAZEUL is facing several issues that are related on the consumer trust on the final build quality of furniture products. Based on the business issue analysis, the solution will focus mainly on improving the performance of internal management and how PAZEUL products gain more credence from the new consumer. A new value proposition, appropriate role in the design, production and marketing division; an appropriate facilities in the wood workshop are the strategy proposed to be the objective of PAZEUL design consultant.An implementation plan on how the strategies will be implemented is shown in the action plan table consist of a 12 months period of time. Some of strategies is implemented immediately and some of the strategies are implemented in a certain period depend on the urgency of the activity.Â Keyword: Architecture, Interior Design, Custom Built Furniture, Consumer Trust.